An alternative approach to the design of multiple beam constrained lens antennas - Uyguroglu, Rasime; Oztoprak, Abdullah Yucel (Tubitak Scientific & Technological Research Council Turkey, 2017)
Rotman lenses are constrained lenses that are used as beam-forming networks to feed array antennas. Their design is based on three focal points, producing three beams with perfect phase fronts. This paper introduces an alternative constrained lens, which has phase equality at five radiating array elements for each beam position. In addition, the center point of the feed curve produces a perfect beam at broadside. The performance of this lens is analyzed and compared to the conventional Rotman lens. The analysis demonstrates that the new lens has better phase performance for wide angle designs. Our study shows that the phase errors of the proposed lens can be as low as half of those produced when using the conventional Rotman lens.
Keywords: Antenna arrays; multiple beams; Rotman lens antennas; phase error; constrained lens antenna